PENGEMBANGAN E - MODUL BANGUN DATAR BERBASIS ARTICULATE STORYLINE 3 UNTUK SISWA KELAS 4 SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics learning tends to focus on the use of textbooks and student worksheets (LKS), which results in a lack of interest in learning among students. Therefore, E-Modules that are tailored to the characteristics and needs of students and can be accessed through facilities available at school are needed. This research aims to develop an Articulate Storyline 3-based E-Module on flat shapes for 4th grade elementary school students. This research applies the ADDIE method, which includes the following stages: Analyze, Design, Development, Implement, and Evaluation. Data collection will rely on instruments such as questionnaires filled out by two experts to test validity and student responses to evaluate practicality. Qualitative and quantitative techniques will be used to analyze the data. The results obtained from expert validation were 93.4% for media experts and 86.1% for subject matter experts. In the effectiveness test using the N-gain score, a score of 0.7 was obtained, while the N-gain percentage was 0.72%. This shows that the E-Module is considered very feasible, very practical, and effective for application in the learning process. Thus, this Articulate Storyline 3-based E-Module can be an innovative solution in the mathematics learning process in elementary schools, especially those focusing on flat shapes.